New Trends in Fuzzy Set Theory and Related Items - Humberto Bustince (Ed.); Esteban Indurain (Ed.); Javier Fernandez (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Since the launch, in 1965, of the key notion of a fuzzy subset by Lotfi A. Zadeh, this concept has succeeded in growing interest and development. Nowadays, it is undoubtedly one of the most powerful and appealing branches of mathematics. Its range of applications is wide and multidisciplinary, starting from computer sciences and artificial intelligence, but also touching on a vast set of scientific disciplines (physics, engineering, medicine, economics, social choice, etc.). The present Special Issue is devoted to introducing new trends on this theory, from an interdisciplinary point of view, and looking for a wide coverage of topics related to fuzzy set and systems.
English
Keywords: Copulas; Image processing; Decision making; Fuzzy relations; Labels; Type-2 fuzzy sets; Fuzzy logic; Aggregation operators; Social choice; Fuzzy sets; Extensions of fuzzy sets; Functional equations; Numerical representability; Ordered structures; General topology